Ideology in Translating Children's Literature into Arabic - Abdelhaq, Seham Moh'd Ahmad (2006)
A Master of Arts Thesis in Translation and Interpreting (Arabic/English) Submitted to the College of Arts and Sciences by Seham Moh'd Ahmad Abdelhaq Entitled, "Ideology in Translating Children's Literature into Arabic," Fall 2006. Available are both Hard and Soft Copies of the Thesis.